Algae as Protein Factories: Expression of a Human Antibody and the Respective Antigen in the Diatom Phaeodactylum tricornutum - Hempel, Franziska (Public Library of Science, 2011)

(untitled)
Microalgae are thought to offer great potential as expression system for various industrial, therapeutic and diagnostic recombinant proteins as they combine high growth rates with all benefits of eukaryotic expression systems. Moreover, microalgae exhibit a phototrophic lifestyle like land plants, hence protein expression is fuelled by photosynthesis, which is CO(2)-neutral and involves only low production costs. So far, however, research on algal bioreactors for recombinant protein expression is very rare calling for further investigations in this highly promising field. In this study, we present data on the expression of a monoclonal human IgG antibody against the Hepatitis B surface protein and the respective antigen in the diatom Phaeodactylum tricornutum. Antibodies are fully-assembled and functional and accumulate to 8.7% of total soluble protein, which complies with 21 mg antibody per gram algal dry weight. The Hepatitis B surface protein is functional as well and is recognized by algae-produced and commercial antibodies.